Sizing and Thermal Stability of Prepared Tetraaminophthalocyaninatocopper(II) Derivatives-grafted Polymers (Baghdad Science Journal, 2016)
Different polymers were prepared by condensation polymerization of sebacic anhydride and adipic anhydride with ethylene glycol and poly(ethylene glycol). Their number average molecular weights were determined by end group analysis. Then, they were grafted on the prepared phthalocyaninatocopper(II) compounds with the general formula (NH2)4PcCu(II) having amino groups of 3,3',3'',3'''- or 4,4',4'',4'''- positions. All prepared polymers, compounds, and phthalocyaninatocopper(II)-grafted polymers were characterized by FTIR. The sizing measurements were carried out in 3,3',3'',3'''- (NH2)4PcCu(II) and 4,4',4'',4'''- (NH2)4PcCu(II) compounds with and without grafting polymers. The results showed that the grafting process led to decreasing in particle size and increasing in surface area. The grafting process was reflected positively on the thermal degradation of 3,3',3'',3'''- (NH2)4PcCu(II) and 4,4',4'',4'''- (NH2)4PcCu(II) grafted polymers. They had higher thermal stability accompanied with higher char residue and T50% weight loss with 3,3',3'',3'''-(NH2)4PcCu(II) and their grafted polymers being the best.